Transformasi Kerajaan Nepo - Makmur, Makmur (Rihlah: Jurnal Sejarah dan Kebudayaan, 2015)
The purpose of this research was to trace the archeological remain of Arung Pattapulo (The Fourty Kings) and the early time of Nepo Kingdom, until the reign of La Bongo as the first King Of Nepo Kingdom. The early guidance in tracing of the source of the historical trail was from Lontara manuscript, then field survey was conducted to excavate the artefact burried. Besides, we also conducted collective society data recording memory (tutur tradition) by interviewing community leader whom related to Arung Pattapulo and the early time of Nepo Kingdom until the reign of La Bongo King. The result was to get the overview of leadership transformation process, the governance system of Nepo Kingdom, the transformation of settlement and agriculture along with the relation of outside community.